DIGITAL INTERVENTIONS FOR THE PREVENTION OF POSTPARTUM DEPRESSION AND ANXIETY: A SCOPING REVIEW - Yayu Handayani Syaidar Putri (Jurnal Keperawatan PPNI Jawa Barat, 2025)
Background: Postpartum depression (PPD) and anxiety are significant public health concerns that affect maternal well-being and child outcomes, with higher prevalence in low- and middle-income countries and among vulnerable groups such as adolescent mothers. Although conventional preventive interventions exist, barriers including stigma, limited access to services, and time constraints often reduce their uptake. Digital health interventions have emerged as promising, scalable alternatives to address these challenges. Objective: This scoping review aimed to map and synthesize existing evidence on digital interventions designed to prevent postpartum depression or anxiety. Methods: A scoping review was conducted following Arksey and O’Malley’s framework and the PRISMA-ScR guidelines. Literature searches were performed in PubMed, CINAHL, and Scopus for studies published between 2020 and 2025. Eligible studies included randomized controlled trials or quasi-experimental designs involving pregnant or postpartum women who received digitally delivered preventive interventions. Methodological quality was appraised using the Joanna Briggs Institute (JBI) checklist. Results: Eight studies met the inclusion criteria, all using randomized controlled designs with sample sizes ranging from 96 to 192 participants. Digital interventions included mobile applications, web-based platforms, messaging or chatbot systems, and virtual reality–based programs. Overall, these interventions demonstrated reductions in depressive and anxiety symptoms, as well as improvements in maternal self-efficacy and engagement. Conclusion: Digital interventions show considerable potential for preventing postpartum depression and anxiety by offering accessible, flexible, and user-centered support. Future research should prioritize cultural adaptation, sustained engagement, and integration into routine maternal healthcare services.